PENGARUH PROMOSI DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN ROKOK A MILD YANG DITAWARKAN OLEH PT DUTA MEDIA INDONESIA AREA PEMATANGSIANTAR (Studi Kasus Pada Konsumen Warung Kopi H Pematangsiantar) - Dwita Suhari Yati Tarigan; Darwin Lie; Efendi Efendi; Erbin Chandra (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2018)
The results of this study can be summarized as follows: 1) Consumers declare that promotion, brand image and purchase decisions A Mild cigarettes are categorized well. 2) Regression analysis result Ŷ = 15,181 + 0,297X1 + 0,765X2, meaning there is positive influence between promotion (X1) and brand image (X2) to decision of purchase (Y) A Mild cigarettes offered by PT Duta Media Indonesia Pematangsiantar Area. 3) Correlation value r = 0,653 which means there is moderately high and positive correlation between promotion, brand image and purchase decision of A Mild cigarettes offered by PT Duta Media Indonesia Pematangsiantar Area. The coefficient of determination is 0,427, meaning that the strongness of purchasing decision is explained by 42,7% by promotion and brand image. 4) Hypothesis Ho rejected, meaning promotion and brand image has a positive and significant effect on the decision of A Mild cigarette purchase offered by PT Duta Media Indonesia Pematangsiantar Area. The suggestion from the research result concludes that A Mild cigarettes offered by PT Duta Media Indonesia Pematangsiantar Area in the influence of purchasing decision, hence company must improve and improve promotion and image of A Mild cigarette brand. The better promotion and brand image of A Mild cigarettes, it will improve the purchase decision of A Mild cigarettes. Keywords: Promotion, Brand Image and Purchase Decision.